ANALISA NILAI VALUASI STARTUP MENGGUNAKAN METODE SCORECARD VALUATION PADA PT SAFAGA INDONESIA - I Gede Nurya Adi Danika Putra Danika Putra Danika (Politeknik Bisnis Indonesia, 2023)
Safaga Indonesia is a startup that operates in the field of educational services to help shape oneself into intelligent, established and useful people who are ready to compete in the world of work, This scorecard valuation is a valuation commonly used by venture capitalists and this valuation is used for companies that do not yet have financial factors such as profits, revenues or gross merchandise value (GMV) and tend to only have ideas, concepts and technology. This research aims to measure the valuation value of startup companies using the PT scorecard method The results of this research show that the startup value of PT. Safaga Indonesia is IDR. 1.818.437.498